The role of G-CSF and IL-6 in the granulopoiesis-stimulating activity of murine blood serum induced by perorally administered ultrafiltered pig leukocyte extract, IMUNOR - Vacek, Antonín; Hofer, Michal; Holá, Jiřina; Weiterová, Lenka; Štreitová, Denisa; Svoboda, Jaroslav (International immunopharmacology, 2007)
IMUNOR, a low-molecular weight (< 12 kD) ultrafiltered pig leukocyte extract, has been previously found to have significant stimulatory effects on murine hematopoiesis supressed by ionizing radiation or cytotoxic drugs. This communication shows data on the mechanisms of these effects. Using ELISA assay, significantly increased levels of granulocyte colony-stimulating factor (G-CSF) and interleukin-6 (IL-6) were observed. On the contrary, no detectable levels of granulocyte-macrophage colony-stimulating factor (GM-CFC) and interleukin-3 (IL-3) have been found in blood serum of IMUNOR-treated mice. Incubation of the serum from IMUNOR-treated mice with antibodies against G-CSF caused abrogation of the ability of the sera to stimulate in vitro growth of colonies originating from granulocyte-macrophage progenitor cells (GM-CFC). In contrast, incubation of the serum with antibodies against IL-6 did not change its colony-stimulating activity. It may be inferred from these findings that G-CSF is probably the main cytokine responsible for the granulopoiesis-stimulating effects of IMUNOR. When the serum from IMUNOR-treated mice with G-CSF inactivated by anti-G-CSF antibodies (but with elevated IL-6) was added to cultures of bone marrow cells together with a suboptimum concentration of IL-3, a significant increase in the numbers of GM-CFC colonies was found. Moreover, conjoint inactivation of G-CSF and IL-6 significantly decreased the numbers of GM-CFC colonies in comparison with those observed when only G-CSF was inactivated. This observation strongly suggests that though IMUNOR-induced IL-6 is not able to induce the growth of GM-CFC colonies alone, it is able to potentiate the hematopoiesis-stimulating effect of IL-3. These findings represent a new knowledge concerning the hematopoiesis-stimulating action of IMUNOR, a promising immunomodulatory agent.
Keywords: prasata; Swine; Hematopoiesis; Interleukin-3; monoklonální protilátky; Stimulation, Chemical; tkáňové extrakty; Tissue Extracts; protilátky blokující; Interleukin-6; granulocyty; chemická stimulace; ELISA; leukocyty; Enzyme-Linked Immunosorbent Assay; Animals; Antibodies, Blocking; ženské pohlaví; interleukin-6; faktor stimulující kolonie granulocytů; zvířata; hematopoéza; Bone Marrow; Leukocytes; kostní dřeň; antisérum; interleukin-3; myši; Financing, Organized; Granulocyte Colony-Stimulating Factor; Granulocytes; Immune Sera; Antibodies, Monoclonal; Mice; Female; financování organizované